Implementasi Model Pembelajaran Project Based Learning (PjBL) Untuk Meningkatkan Hasil Belajar PJOK Materi Bulutangkis Siswa Kelas X2 SMA Negeri 1 Tabanan - Komang Adhi Pramana Putra; Ketut Semarayasa; Ni Luh Putu Spyanawati (Journal of Innovative and Creativity, 2026)
Student learning outcomes in badminton material, especially in forehand and backhand service techniques are still not optimal. Therefore, an innovative learning model is needed to improve student learning outcomes. This study aims to improve the learning outcomes of Physical Education (PJOK) in badminton material on basic backhand and forehand service techniques for class X2 of SMA Negeri 1 Tabanan by implementing the project based learning (PjBL) learning model. The type of research used is Classroom Action Research. The subjects of this study were students of class X2 of SMA Negeri 1 Tabanan consisting of 18 boys and 22 girls. Data collection techniques in this study were carried out using test instruments and performance tests. Based on the analysis of cycle I data, the results of 1 student (2.5%) were in the very poor category, 25 students (62.5%) were poor, 27 students (35%) were sufficient and 3 students (7.5%) were good. After the improvement of cycle II, the learning outcomes increased by 7 students (17.5%) very good, 31 students (77.5%) good, 1 student (2.5%) sufficient and 1 student (2.5%) less. Classical completeness in cycle II increased by 95%. The conclusion of this study is that the implementation of the project based learning (PjBL) learning model has proven effective in improving the learning outcomes of Physical Education (PJOK) in badminton material for class X2 students of SMA Negeri 1 Tabanan, so that this model can be used as an alternative in the PJOK learning process to improve students' understanding and skills optimally. This study is expected to be a reference material for implementing the PjBL model in the learning process, especially in the PJOK subject on the badminton game material. It is recommended that PJOK teachers can apply the PjBL learning model because it has been proven to have a significant effect on student learning outcomes.